Adubação silicatada em hortaliças não convencionais - Oliveira, Luís Cláudio Pessoa (2017)
The importance of unconventional vegetables in the diet, culture and economy of traditional rural populations is unquestionable. However, there are few studies on these plants in Brazil. Considering the silicon beneficial effects on human health, as well as for several commercially exploited crops, being little explored in vegetables, the studies related to the mineral nutrition of vegetables unconventional with the mineral, will not only indicate the effects on the growth practice and mineral composition of these plants, but also contribute to the rescue and who knows, reintroduction of these species in the diet of Brazilians. The objective of this study was to identify unconventional vegetable species responsive to silicate fertilization, as well as to verify the effect of this fertilization on mineral and macronutrient content and on plant growth. Two experiments were carried out. In the first experiment an exploratory study was carried out with 9 species of unconventional vegetables (Maranta arundinaceaea L., Rumex acetosa L., Amaranthus spinosus L., Amaranthus viridis L., Amaranthus retroflexus L., Amaranthus deflexus L., Amaranthus hybridus L., Stachys byzantina and Sonchus oleraceus L.), combined with 2 doses of Si (0 and 50 mg dm -3 of Si), being evaluated the silicon content in plants, fresh and dry mass. In the second experiment were evaluated four species more responsive to silicate fertilization and of greater interest for use in the human diet, selected in the first study (Rumex acetosa, Amaranthus retroflexus L., Sonchus oleraceus L. and Stachys byzantina), combined with 5 doses of Si (0, 25, 50, 100 and 150 mg dm -3 Si). Plant architecture, relative chlorophyll index, fresh and dry masses, silicon content and macronutrients were evaluated. The tests were carried out in a greenhouse belonging to the UFLA Olericulture Sector. The completely randomized design (DIC) with four replications in a factorial scheme was used in both experiments. The species Amaranthus retroflexus L., Sonchus oleraceus L. and Stachys byzantina presented the highest levels of Si; the application of doses higher than 100 mg dm -3 promoted the highest silicon contents estimated for the species under study; silicate fertilization does not influence green and dry matter; silicate fertilization increases the levels of phosphorus, calcium, magnesium, potassium and chlorophyll; the species, Amaranthus retroflexus L., Rumex acetosa L., and Stachys byzantina, are classified as non-silicon accumulators, while the species Sonchus oleraceus L. is classified as an intermediate.